2018
DOI: 10.1039/c8ew00258d
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficients in sewer force main biofilms treated with iron salts

Abstract: Iron treatment of wastewater in sewer force mains for sulfide abatement reduces biofilm diffusivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…If the flow velocity in a pressure main frequently exceeds 0.8-1 m s −1 , the corresponding biofilm is relatively smooth and thin, typically 100-300 µm (USEPA, 1974). However, high flow velocities also reduce the diffusion layer at the biofilm-water interface and thereby the resistance against transport of substrates and products (Kiilerich et al, 2018a). In total, a high flow velocity will normallyconsidering constant residence timereduce the potential for sulfide formation in pressure mains.…”
Section: Flow Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…If the flow velocity in a pressure main frequently exceeds 0.8-1 m s −1 , the corresponding biofilm is relatively smooth and thin, typically 100-300 µm (USEPA, 1974). However, high flow velocities also reduce the diffusion layer at the biofilm-water interface and thereby the resistance against transport of substrates and products (Kiilerich et al, 2018a). In total, a high flow velocity will normallyconsidering constant residence timereduce the potential for sulfide formation in pressure mains.…”
Section: Flow Velocitymentioning
confidence: 99%
“…The reactions are, in practice, complex and dependent on pH, concentrations of iron and sulfide, redox potential and the microbial composition of the wastewater (Kiilerich et al, 2018b;Nielsen et al, 2005aNielsen et al, , 2008. It has furthermore been observed that the use of iron salts may reduce the diffusion of the sewer biofilm (Kiilerich et al, 2018a). In spite of the complex nature of the reaction kinetics, in practice the use of iron salts for sulfide control is rather simple, efficient and relatively cheap.…”
Section: Iron Salt Additionmentioning
confidence: 99%